2013
DOI: 10.2174/1874104501307010001
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Hydroxyethylene-Based BACE-1 Inhibitors Incorporating Extended P1 Substituents

Abstract: Novel BACE-1 inhibitors with a hydroxyethylene central core have been developed. Modified P1´ and extended P1 substituents were incorporated with the aim to explore potential interactions with the S1´ and the S1-S3 pocket, respectively, of BACE-1. Inhibitors were identified displaying IC50 values in the nanomolar range, i.e. 69 nM for the most potent compound. Possible inhibitor interactions with the enzyme are also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 18 publications
(23 reference statements)
0
8
0
Order By: Relevance
“…The most potent compound among the 30 compounds developed in this series was compound 3 that exhibited a remarkable IC 50 value of 69 nM. 55 This compound possesses bulkier substituents on the hydroxyethelene skeleton compared with other compounds in the same series, which indicated that the binding site of the enzyme at P1 and P3 dispositions could accommodate such large moieties. Nonetheless, this promising activity was not supported by the cell binding assay results that showed a very low percentage of inhibition (ca.…”
Section: Peptidomimetic Bace1 Inhibitorsmentioning
confidence: 90%
See 3 more Smart Citations
“…The most potent compound among the 30 compounds developed in this series was compound 3 that exhibited a remarkable IC 50 value of 69 nM. 55 This compound possesses bulkier substituents on the hydroxyethelene skeleton compared with other compounds in the same series, which indicated that the binding site of the enzyme at P1 and P3 dispositions could accommodate such large moieties. Nonetheless, this promising activity was not supported by the cell binding assay results that showed a very low percentage of inhibition (ca.…”
Section: Peptidomimetic Bace1 Inhibitorsmentioning
confidence: 90%
“…In other work, a series of hydoxyethylene‐based compounds were synthesized with the aim to discover the potential interactions with BACE1 S1 and S3 binding subpockets. The most potent compound among the 30 compounds developed in this series was compound 3 that exhibited a remarkable IC 50 value of 69 nM . This compound possesses bulkier substituents on the hydroxyethelene skeleton compared with other compounds in the same series, which indicated that the binding site of the enzyme at P1 and P3 dispositions could accommodate such large moieties.…”
Section: Bace1 As a Potential Target For The Treatment Of Alzheimer'smentioning
confidence: 93%
See 2 more Smart Citations
“…In an effort to increase cell permeability by reducing polarity, compound 35 was designed. 142 Despite the rather large lipophilic P1 ligand, this compound showed a BACE1 IC 50 of 69 nM. Unfortunately, this compound did not display cellular potency.…”
Section: Design Of Peptidomimetic Bace1 Inhibitorsmentioning
confidence: 94%